The Alignment of Internal and External Audit Agencies in Administering Public Sector Audits in Indonesia - Genda, Maming; Yani, Ahmad; Syafiin, Rezky Amalia (PT Penjaminan Infrastruktur Indonesia (Persero), 2024)
The management of public finance to achieve national prosperity requires the effective, efficient, and integrated work of the existing audit boards. Therefore, continuous evaluation of the alignment of internal and external audit agencies is essential to ensure reliable public financial management and prevent corruption. This study describes the performance and coordination patterns between internal and external audit agencies by detailing their synchronization patterns in administering financial audits in the Indonesian public sector. Using a normative legal research method, the study incorporates legislative and conceptual approaches. The findings reveal that the performance of both internal and external audit agencies in safeguarding public finance from fraud shows varied degrees of effectiveness. However, a comprehensive regulatory framework governing the alignment of these agencies remains absent. Furthermore, synchronization in public finance audits is pursued through a unified regulatory framework, horizontal alignment among agencies, and the establishment of clear boundaries of authority and coordination mechanisms between the internal and external audit agencies. Further research should consider the potential for consolidating various regulations of public sector audits through an omnibus law approach.